Strategi Pemasaran Kain Songket Di Sumatera Selatan - Prayoga Pidrosa; Rizki Pratama; M. Eko Saputra D. D; Tata Sutabri (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Palembang Songket Cloth is one of the cultural works of South Sumatra which is included in the list of Indonesian Intangible Cultural Heritage. As the era of songket cloth has developed into a profitable business opportunity, and marketing strategy is the most important factor in business because this is what determines everything, the increasing competition in the business world means that all business actors must be able to think creatively and innovatively to attract consumer interest. Therefore, the author is looking for marketing strategies for songket cloth in South Sumatra, one of which is located at Griya Kain Tuan Kentang, Jakabaring District, Palembang City. Based on the results of Griya Kain Tuan Kentang Palembang's research in the field directly with the people involved as well as observing aspects of the product, location, advertising, price, process, physical evidence, it can be concluded that it is functioning or running well. And the author suggests that Griya Kain Tuan Kentang needs to innovate or initiate so that it is more widely known by consumers, for example participating in events such as exhibitions and markets.